Comparison of immunologic responses following intranasal and oral administration of a USDA-approved, live-attenuated Streptococcus equi vaccine - Delph, Katherine (Kansas State University, 2016)
Background: While there is a commercially-available vaccine for Streptococcus equi subsp. equi licensed for the intranasal route of administration, some equine practitioners are administering this vaccine orally despite a lack of evidence for its efficacy by this route of administration. Objectives: To compare systemic and local immune responses following intranasal or oral administration of the USDA-approved, live-attenuated Streptococcus equi subspecies equi vaccine (Pinnacle IN®, Zoetis, Florham Park, New Jersey). Study Design: Experimental, randomized clinical trial Methods: Eight healthy horses with low Streptococcus equi M protein (SeM) titers (<1:1600) were randomly assigned to an intranasal or oral two-vaccine series. SeM-specific serum immunoglobulins G (IgG) and A (IgA) and nasal secretion IgA were assessed using a commercially-available ELISA (Equine Diagnostic Solutions, LLC, Lexington, Kentucky) and a novel magnetic microsphere assay utilizing fluorescence. A general linear mixed models approach was used for statistical data analysis. Results: As expected, intranasal vaccinates showed substantial increases in both serum SeM-specific IgG and IgA levels post-vaccination (P=0.0006 and P=0.007, respectively). Oral vaccinates showed an increase in serum SeM-specific IgG post-vaccination (P=0.0150), though only one-third the magnitude of intranasal vaccinates. Oral vaccinates showed no evidence of change in SeM-specific IgA post-vaccination (P=0.15). Main Limitations: Changes in mucosal antibody responses were not identified in this study which may be related to small change in antibody response, timing of sample collection, or method of nasal secretion collection. Conclusions: Results indicate that intranasal or oral vaccine administration resulted in increased serum SeM-specific IgG, though the magnitude of response differed between routes.
Keywords: Streptococcus equi subsp equi; vaccination; horse; mucosal immunity; SeM titer